2019
DOI: 10.21873/anticanres.13682
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Breast Cancer Patients Who Refuse Surgery

Abstract: Aim: This study describes the demographic, socioeconomic, and tumor-specific characteristics of patients who refuse breast cancer surgery. Materials and Methods: This is a retrospective study of breast cancer patients from 2004-2015 captured by the National Cancer Data Base. Demographic, socioeconomic, and tumor-specific predictors were compared between patients who refused breast cancer surgery versus those who agreed to surgery, using bivariate and multivariate models. Results: A total of 2,445,870 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 12 publications
0
26
0
Order By: Relevance
“…Among the 82 patients who underwent surgical evaluation for SBL, no significant statistical differences were found between PRE-COVID-19-SBL and POST-COVID-19-SBL groups regarding personal and anamnestic data like age, diameter of SBL, personal and family history of BC. Table I summarizes the findings showing homogeneity in both groups regarding these potential confounding factors (18)(19)(20)(21). Grouping population according to BI-RADS lexicon showed no statistically significant differences between the two different periods of analysis.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Among the 82 patients who underwent surgical evaluation for SBL, no significant statistical differences were found between PRE-COVID-19-SBL and POST-COVID-19-SBL groups regarding personal and anamnestic data like age, diameter of SBL, personal and family history of BC. Table I summarizes the findings showing homogeneity in both groups regarding these potential confounding factors (18)(19)(20)(21). Grouping population according to BI-RADS lexicon showed no statistically significant differences between the two different periods of analysis.…”
Section: Resultsmentioning
confidence: 94%
“…Even in normal times, fear and anxiety play a major role in the course of patients' disease. About 0.64% of BC patients refuse surgical treatment according to SEER database (19,21). Personal and socioeconomic conditions were linked to surgical treatment refusal, including higher age at diagnosis, female gender, Ethnicity, type of insurance, LABC (stage II and III BC), non-triple-negative breast cancer, residence areas with a low percentage of high school diplomas (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, disparities affecting breast cancer patients are not limited to autologous reconstruction. Our group has shown that the rate of breast reconstruction, refusal of surgical treatment, and the survival of male patients with breast cancer has also been shown to be affected by ethnic and demographic characteristics [ 21 , 22 , 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…[37][38][39] Previous reports identi ed that Black and Asian patients, those who live alone, were unmarried or did not have children, had government issued insurance, or had issues performing their activities of daily living were more likely to decline all treatment. [40,41] Although our study includes data on a large number of PDAC patients, there are limitations. Importantly, the use of immunotherapy is not common therefore the IT-CT treatment group is small in comparison to those who received CT alone.…”
Section: Discussionmentioning
confidence: 99%